A quantum leap in finance - European Investment Bank (European Investment Bank, 2023)
Quantum technologies offer a vision of a healthier, more sustainable and resilient Europe. They will one day enable disruptive innovations that could transform our societies, economies and almost all industries by solving problems that have eluded even our most powerful computers. From chemicals and life sciences to finance and renewable energy, quantum technologies can speed up the development of groundbreaking new products and improve the ways we do things now.But despite a world-leading academic foundation in quantum technologies, European quantum companies consistently lag behind global peers. The European Union is home to 25% of all quantum companies worldwide, but accounts for less than 5% of global funding. Companies struggle to scale commercial operations due to a lack of knowledgeable investors or commercial partners.This study aims to answer the key questions about the future of quantum technologies: What can we expect from groundbreaking innovations? Why should we already begin to boost investment into the nascent European quantum industry? How can we speed up the development of the industry in Europe? We recommend a mix of policy and financing measures to accelerate the journey from academic knowledge to large-scale commercial success.